Determinants of Demoralization Syndrome and Social Support Among Patients with Breast Cancer: A Cross-Sectional Study - Yang L; Song LX; Zhang L; Yang Y; Zhang YM (Journal of Multidisciplinary Healthcare)
Li Yang,1,2 Ling-Xia Song,1 Lin Zhang,1,2 Yan Yang,1 Yong-Mei Zhang1 1Department of Nursing, The Affiliated Hospital of Zunyi Medical University, Zunyi, 563000, People’s Republic of China; 2Department of General Surgery, The Affiliated Hospital of Zunyi Medical University, Zunyi, 563000, People’s Republic of ChinaCorrespondence: Yong-Mei Zhang, Department of Nursing, The Affiliated Hospital of Zunyi Medical University, No. 149, Dalian Road, Huichuan District, Zuny, GuiZhou, People’s Republic of China, Tel +86 15185210524, Fax +86 851-28608909, Email 583726149@qq.comObjective: This study aimed to assess the determinants of demoralization syndrome among patients with breast cancer (BC) in the southwestern region of China.Methods: This investigation constituted a single-center cross-sectional study in which 176 patients with BC were surveyed through a questionnaire covering the current status of demoralization syndrome and social support.Results: Majority of patients with BC developed moderate-to-severe levels of demoralization. The degree of demoralization among patients with BC was complex and influenced by a variety of factors. Among patients with BC, demographic variables such as age, education level, residential address, monthly income, occupation, and receipt of chemotherapy were the main influencing factors (P < 0.05), whereas factors such as current status of children, and surgical methods were not the main influencing factors (P < 0.05). Additionally, all patients with BC reported receiving social support exceeding moderate levels, with no statistically significant difference in demographic data observed among those reporting heightened levels of social support (P > 0.05).Conclusion: There are many factors influencing the degree of demoralization among patients with BC. Nursing interventions play a pivotal role in minimizing demoralization among patients with BC. We should pay more attention to patients with determinants of commitment level. Positive communication with patients, involving attentive listening, guidance and encouragement, is essential for providing effective psychological care and social support, fostering trust between healthcare providers and patients.Keywords: breast cancer, demoralization syndrome, social support